Implementation of Stimulation, Early Detection, and Intervention Programs for Monitoring the Growth and Development of Children Aged 2-3 Years - Lestari, Mega Cahya Dwi; Ayu Citra Dewi; Sri Intan Wahyuni; Juliwis Kardi; Yendri Junaidi; Alif Laini (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Starting from growth that supports development, in the end growth and development go hand in hand. An important period in a child's growth and development begins in infancy because basic growth is what will influence and determine the child's subsequent development. The aim of this research is to detect deviations in the development of early childhood children aged 2-3 years at the ECCE Rahmah El Yunusiyyah Padang Panjang through the Stimulation, Detection and Early Intervention of Child Growth and Development (SDICGD) instruments in the Android feature. This research was conducted using a cross-sectional approach. Participants in this study were 26 children aged 2-3 years using a consecutive sampling technique of 10 children whose growth and development were monitored using the SDICGD android application. The results of this study showed that several partisipants experienced malnutrition, one partisipant out of nine normal partisipants. The Developmental Pre-Screening Questionnaire (DPSQ) instrument of the ten child participants contained nine children (90%) who were according to the developmental stage aged 24-36 months, and one child was not according to the developmental stage. The results of the Attention Deficit and Hyperactivity Disorder (ADHD) test showed that three children (60%) were normal, and two children (40%) were hyperactive. Early detection of children's growth and development must be carried out regularly every month, and according to the child's age. For further research, it is hoped that early detection will also be carried out on the development of children's mental health, not just growth and development which is common and widely researched. Schools and parents must play an active role in children's growth and development so that no developmental stages are missed, and children grow and develop according to their age. Keywords: simulation, detection, early intervention, child growth and development, development of children aged 2-3 years References: Arinny, L. (2023). Deteksi Dini Masalah Perilaku Psikososial Pada Remaja Di Sekolah Menengah Atas Kota Semarang. Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 12(1), 67–74. https://stikes-nhm.e-journal.id/NU/article/view/1749 Dunkel, Luque, Loche, & Savage. (2021) ‘Digital technologies to improve the precision of pediatric growth disorder diagnosis and management’, Growth Hormone and IGF Research, 59, p. 101408. https://doi.org/10.1016/j.ghir.2021.101408. Endo, D. (2014). Monitoring the Growth and Development of Toddlers Using Ma-ternal and Child Health Book. Kesmasindo, Volume 6 N, 166–175. Fitriani, I. S., & Oktobriariani, R. R. (2017). Stimulasi, Deteksi dan Intervensi Dini Orang Tua terhadap Pencegahan Penyimpangan Pertumbuhan dan Perkembangan Anak Balita. Indonesian Journal for Health Sciences, 1(1), 1. https://doi.org/10.24269/ijhs.v1i1.383 Friska, E. and Andriani, H. (2022) ‘The Utilization of Android-Based Application as a Stunting Prevention E-Counseling Program Innovation during Covid-19 Pandemic’, Journal of Maternal and Child Health, 6(5), pp. 323–332. https://doi.org/10.26911/thejmch.2021.06.05.02. González-Pérez, Matey-Sanz, Granell, Díaz-Sanahuja, Bretón-López, & Casteleyn. (2023) ‘AwarNS: A framework for developing context-aware reactive mobile applications for health and mental health’, Journal of Biomedical Informatics, 141(October 2022), p.104359. https://doi.org/10.1016/j.jbi.2023.104359. Gusvita, Y. (2024). Program PAUD Rahmah El Yunusiyyah. Hibana, H., & Surahman, S. (2021). Optimalisasi Perkembangan Anak Melalui Deteksi Dini Tumbuh Kembang Anak. Qurroti : Jurnal Pendidikan Islam Anak Usia Dini, 3(1), 42–55. https://doi.org/10.36768/qurroti.v3i1.150 IDAI. (2013). Recognizing Common Developmental Delays in Children. http://www.idai.or.id/article/seputar-kesehatan-anak/mengenal-keterlamatan-perkembangan-umum-pada-anak Inggriani, D. M. (2019). “Early Detection of Growth and Development of Children Aged 0-6 Years Based on Android Applications.” STIKES Adila Journal, Volume 1,. Inggriani, D. M., Rinjani, M., & Susanti, R. (2019). Deteksi Dini Tumbuh Kembang Anak Usia 0-6 Tahun Berbasis Aplikasi Android. Wellness And Healthy Magazine, 1(1), 115–124. https://wellness.journalpress.id/wellness/article/download/w1117/65 Kozhevnikov, M. (2007). Cognitive Styles in the Context of Modern Psychology: Toward an Integrated Framework of Cognitive Style. Psychological Bulletin, 133(3), 464–481. https://doi.org/10.1037/0033-2909.133.3.464 Kozier, Erb, Berman, & S. (2015). Nursing Fundamentals Textbook: Concepts, Processes, Practices .: Vol. (7th ed.,. EGC. Langarizadeh, M. et al. (2021) ‘Mobile apps for weight management in children and adolescents; An updated systematic review’, Patient Education and Counseling, 104(9), pp. 2181–2188. https://doi.org/10.1016/j.pec.2021.01.035. Mahyumi Rantina, Dra. Rahmanela, Y. K. N. (2021). Buku Stimulasi Dan Deteksi Dini Tumbuh Kembang Anak (0-6Tahun). EDU Publisher. https://books.google.co.id/books?id=raEJEAAAQBAJ&lpg=PP3&pg=PP1#v=onepage&q&f=false Marwasariaty, M., Sutini, T., & Sulaeman, S. (2019). Pendidikan Kesehatan Menggunakan Media Booklet + Aplikasi SDIDTK Efektif Meningkatkan Kemandirian Keluarga dalam Pemantauan Tumbuh Kembang Balita. Journal of Telenursing (JOTING), 1(2), 236–245. https://doi.org/10.31539/joting.v1i2.853 Nahar, B. et al. (2020) ‘Early childhood development and stunting: Findings from the MAL-ED birth cohort study in Bangladesh’, Maternal and Child Nutrition, 16(1). Available at: https://doi.org/10.1111/mcn.12864. Nesy, A. M., & Pujaningsih, P. (2023). Deteksi Dini Tumbuh Kembang pada Anak Usia Pra Sekolah. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 7(4), 4682–4689. https://doi.org/10.31004/obsesi.v7i4.4517 Nursalam. (2014). Nursing Care for Infants and Children. Salemba Medika. Pandita, A., Sharma, D., Pandita, D., Pawar, S., Tariq, M., & Kaul, A. (2016). Childhood obesity: prevention is better than cure. Diabetes, metabolic syndrome, and obesity: targets and therapy, 9, 83–89. https://doi.org/10.2147/DMSO.S90783. Patel, A.B. et al. (2019) ‘M-SAKHI—Mobile health solutions to help community providers promote maternal and infant nutrition and health using a community-based cluster randomized controlled trial in rural India: A study protocol’, Maternal and Child Nutrition, 15(4), pp. 1–16. https://doi.org/10.1111/mcn.12850 Rahayu, S. F., Anggeriyane, E., & Mariani, M. (2021). Efforts to Strengthen Stimulation, Detection and Early Development and Development Program (SDIDTK) Through Anthropometric Examination in Preschool Children. Jurnal EMPATI (Edukasi Masyarakat, Pengabdian Dan Bakti), 2(1), 71. https://doi.org/10.26753/empati.v2i1.522 Roba, A.A. et al. (2021) ‘Prevalence and determinants of concurrent wasting and stunting and other indicators of malnutrition among children 6–59 months old in Kersa, Ethiopia’, Maternal and Child Nutrition, 17(3), pp. 1–12. https://doi.org/10.1111/mcn.13172. Sari, K. and Sartika, R.A.D. (2021) ‘The effect of the physical factors of parents and children on stunting at birth among newborns in Indonesia’, Journal of Preventive Medicine and Public Health, 54(5), pp. 309–316. https://doi.org/10.3961/jpmph.21.120. SDIDTK. (2016). Pedoman Pelaksanaan Stimulasi, Deteksi dan lntervensi Dini Tumbuh Kembang Anak. Direktorat Kesehatan Departmen Kesehatan Keluarga, 59. Shofiyati, et al. (2022). The Role of Teachers in Online Learning for Early Childhood Children in the Covid-19 Pandemic Era. Golden Generation: Journal of Ear-Ly Childhood Islamic Education., Vol. 5 No.https://journal.uir.ac.id/index.php/generationemas/article/view/8891 Shrestha, M.L. et al. (2022) ‘Malnutrition matters: Association of stunting and underweight with early childhood development indicators in Nepal’, Maternal and Child Nutrition, 18(2), pp. 1–9. https://doi.org/10.1111/mcn.13321. Soetjiningsih. (2014). Child Development. EGC. Suharsimi Arikunto. (2014). Prosedur Penelitian Suatu Pendekatan Praktik. Rineka Cipta. Suprayitno, E., Yasin, Z., Kurniati, D., & Rasyidah. (2021). Peran Keluarga Berhubungan dengan Tumbuh Kembang Anak Usia Pra Sekolah. Journal of Health Science, VI(II), 63–68. Tanuwijaya, S. (2014). General Concept of Growth and Development. EGC. Vanderloo, L.M. et al. (2021) ‘Selecting and evaluating mobile health apps for the healthy life trajectories initiative: Development of the eHealth resource checklist’, JMIR m Health and uHealth, 9(12), pp. 1–8. https://doi.org/10.2196/27533. Wahyudin, T. E. (2021). Handbook for Stimulation and Detection of Child Growth and Development (0-6 Years). EDU Publisher. Wahyuni, T. (2019). Diagnostic Test of the Mother Cares Application (Moca) for Early Detection of the Risk of Developmental Deviations in Toddlers. Unsika Journal, Vol 4 No 1. Winda Windiyani, Sri Wahyuni, E. N. P. (2020). STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG ANAK. EDU Publisher. Wulandari, U. R., Budihastuti, U. R., & Poncorini, E. P. (2017). Analysis of Life-Course Factors Influencing Growth and Development in Children under 3 Years Old of Early Marriage Women in Kediri. Journal of Maternal and Child Health, 02(02), 137–149. https://doi.org/10.26911/thejmch.2017.02.02.05